Green synthesis of silver nanoparticles mediated by neem leaves extract as antifungal agent against fungi isolated from water treatment - Wan Nur Atiqah, Wan Shamsudin (2023)
Fungal contamination in the drinking water distribution system (DWDS) can generate taste and odor issues, ultimately affecting the quality of the delivered water. Thus, possibly causing a significant threat to public health. Rhodotorula mucilaginosa and Aspergillus sp. is one of the current emerging opportunistic waterborne pathogens isolated from DWDS that can colonize and infect immunocompromised individuals. The usage of chemical treatment to remove this pathogen may also leave disinfectant residuals, which are known for their toxicity, and rather, such an approach can be too expensive in some countries. This circumstance generated interest to develop an alternative disinfectant in water treatment which is more effective with less toxicity. This study attempted to use neem leaves extract (NLE) and environmentally friendly green synthesized silver nanoparticles mediated by neem leaves extract (NLE-AgNPs) as an alternative natural-based disinfectant or antifungal agent against both isolated fungi. The formation of NLE-AgNPs was confirmed through several characterization processes, including ultraviolet-visible spectroscopy (UV-Vis), Fourier-transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), Field emission scanning electron microscope (FESEM), and Transmission electron microscope (TEM) analysis. The result revealed that the NLE-AgNPs showed UV-vis spectra peak around 421 nm, are crystalline in nature, uniformly well distributed and have a spherical morphology with an average size of 20.13 - 23.05 nm in diameter. NLE-AgNPs exhibit excellent antifungal activity against both waterborne pathogens on agar well diffusion assay and water disinfection test (fungal inactivation test) as compared to NLE alone. The inactivation mechanism was described based on the FESEM image analysis of untreated and treated fungi from the water disinfection test, which revealed structural damage and deformation of fungus when treated with NLE-AgNPs, causing retardation of fungus growth for further reproduction. The inactivation of fungi seeded in sample water treated with NLE-AgNPs was further optimized by response surface methodology (RSM) using the Design Expert software (Stat-Ease Inc., Minneapolis, MN 55413, USA, version 7.0.0). The effect of NLE-AgNPs dosage (10-100 μg/L), pH (6-8), contact time (40-240 min), as well as mixing speed (100–120 rpm) was studied on fungal inactivation performance in RSM. Full factorial design (FFD) was employed to determine and screen the experimental variables that significantly influence fungal inactivation efficiency. The initial screening indicated that dosage, contact time, and pH are the most significant factors affecting the fungal inactivation process, with a maximum response of 39.07%. These significant factors were optimized using Central Composite Design (CCD) and the optimum condition of the dosage, pH, and contact time were found to be 105 μg/L, pH 6.5, and 245 minutes, respectively at which the fungal inactivation response maximize up to 51.03%. R2 for fungal inactivation process by using CCD results in a figure of 0.9478, indicating a good agreement between model experimental data and forecasting data. The results of this study provide insight into the potential of neem leaf extracts and their derivatives, biosynthesis NLE-AgNPs, as an alternative eco-friendly disinfectant and antifungal agents in water treatment.